2015
DOI: 10.1515/jpm-2015-0044
|View full text |Cite
|
Sign up to set email alerts
|

Clinical chorioamnionitis at term III: how well do clinical criteria perform in the identification of proven intra-amniotic infection?

Abstract: Objective The diagnosis of clinical chorioamnionitis is based on a combination of signs [fever, maternal or fetal tachycardia, foul-smelling amniotic fluid (AF), uterine tenderness, and maternal leukocytosis]. Bacterial infections within the amniotic cavity are considered the most frequent cause of clinical chorioamnionitis and an indication for antibiotic administration to reduce maternal and neonatal morbidity. Recent studies show that only 54% of patients with the diagnosis of clinical chorioamnionitis at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
66
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 68 publications
(71 citation statements)
references
References 135 publications
2
66
0
3
Order By: Relevance
“…Studies have demonstrated a correlation between maternal fever and the development of fetal tachycardia [34]. However, fetal tachycardia, even in the presence of maternal fever, is poorly correlated with intra-amniotic infection [3335].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated a correlation between maternal fever and the development of fetal tachycardia [34]. However, fetal tachycardia, even in the presence of maternal fever, is poorly correlated with intra-amniotic infection [3335].…”
Section: Discussionmentioning
confidence: 99%
“…The implications of a high inaccuracy rate in the diagnosis of preterm clinical chorioamnionitis could be serious because the standard intervention is the induction of labor [64]. …”
Section: Commentmentioning
confidence: 99%
“…Acute histologic chorioamnionitis was diagnosed by the presence of acute inflammatory changes observed in the tissue samples collected from the amnion, chorion-decidua, umbilical cord, and chorionic plate [192, 196, 197, 200202]. Clinical chorioamnionitis was diagnosed by the presence of maternal fever (temperature >37.8°C) accompanied by two or more of the following criteria: 1) maternal tachycardia (heart rate >100 beats/min); 2) uterine tenderness; 3) foul-smelling amniotic fluid; 4) fetal tachycardia (heart rate >160 beats/min); and 5) maternal leukocytosis (leukocyte count >15,000 cells/mm 3 ) [203211]. …”
Section: Methodsmentioning
confidence: 99%